In Vitro Selection of a Single-Stranded DNA Molecular Recognition Element Specific for Bromacil - Williams, Ryan M.; Kulick, Amanda R.; Yedlapalli, Srilakshmi; Battistella, Louisa; Hajiran, Cyrus J.; Sooter, Letha J. (Journal of Nucleic Acids, 2014)
Bromacil is a widely used herbicide that is known to contaminate environmental systems. Due to the hazards it presents and inefficient detection methods, it is necessary to create a rapid and efficient sensing device. Towards this end, we have utilized a stringent in vitro selection method to identify single-stranded DNA molecular recognition elements (MRE) specific for bromacil. We have identified one MRE with high affinity (Kd=9.6 nM) and specificity for bromacil compared to negative targets of selection and other pesticides. The selected ssDNA MRE will be useful as the sensing element in a field-deployable bromacil detection device.